Literatur Review Peran Plasenta terhadap Janin pada Ibu Hamil dengan COVID-19 - Eka, Restu Ayu; Wani, Elsayanti (Indonesian Journal of Biomedical Science and Health, 2021)
Coronavirus adalah penyebab penyakit menular yang baru ditemukan dikenal sebagai COVID-19, gambaran klinis COVID-19 mirip dengan wabah sebelumnya yaitu Middle East Respiratory Syndrome (MERS) dan Severe Acute Respiratory Syndrome (SARS). Kematian COVID-19 sebagian besar disebabkan Acute Respiratory Distress Syndrome (ARDS), sel endotel paru memiliki peran penting jika terjadi ARDS, sel endotel yang mengalami peradangan karena gangguan pernafasan akan mencegah koagulasi melalui ekspresi faktor antikoagulan. Wanita hamil mempunyai resiko dan komplikasi lebih parah jika terinfeksi virus corona dan diidentifikasi sebagai kelompok yang rentan terhadap virus COVID-19. Kondisi Ibu hamil yang terinfeksi virus COVID-19 pada plasenta menunjukkan adanya tanda-tanda intervilus akut dan perdangan kronis dengan status peradangan yang parah dipicu karena infeksi virus COVID-19. Plasenta dari ibu yang terkena COVID-19 menunjukkan temuan patologis berupa intervillositis, Angiotensin converting enzyme 2 (ACE2) yang dikenal sebagai reseptor COVID-19. Plasenta juga berperan penting terhadap barrier dari infeksi virus lapisan vili yang berada disekitar plasenta mempunyai peran untuk melindungi janin dari infeksi virus. Virus COVID-19 dapat menyebabkan komplikasi selama kehamilan dan efek pada janin, oleh karena itu penting mengetahui peran plasenta pada ibu hamil yan terinfeksi virus COVID-19.   Coronavirus is the cause of a newly discovered infectious disease known as COVID-19, the clinical picture of COVID-19 is similar to previous outbreaks namely Middle East Respiratory Syndrome (MERS) and Severe Acute Respiratory Syndrome (SARS). Most of the deaths from COVID-19 are caused by Acute Respiratory Distress Syndrome (ARDS), pulmonary endothelial cells have an important role in the event of ARDS, endothelial cells that experience inflammation due to respiratory disorders will prevent coagulation through the expression of anticoagulant factors. Pregnant women have a greater risk and complications if they are infected with the corona virus and are identified as a group that is vulnerable to the COVID-19 virus. The condition of pregnant women infected with the COVID-19 virus in the placenta shows signs of acute intervillous and chronic inflammation with a severe inflammatory status triggered by infection with the COVID-19 virus. The placenta from mothers affected by COVID-19 showed pathological findings in the form of intervillositis, Angiotensin converting enzyme 2 (ACE2), known as the COVID-19 receptor. The placenta also plays an important role in the barrier against viral infection. The villous layer around the placenta has a role to protect the fetus from viral infection. The COVID-19 virus can cause complications during pregnancy and effects on the fetus, therefore it is important to know the role of the placenta in pregnant women infected with the COVID-19 virus.Pregnancy creates a unique immunological paradox, the immune system in the mother must undergo adaptation to the fetus while simultaneously maintaining a strong defense against pathogenic infections, besides that in pregnant women also change the immune system from Th1 to Th2 direction. Th2 is a lymphocyte cell that produces anti-inflammatory cytokines namely Il-4, Il-10, Il-3 and TGFß therefore, pregnant women are more susceptible to Corona virus infection. The role of vitamin supplementation is important dietary component as antioxidant and immunomodulatory effects.